2022
DOI: 10.1007/s12687-021-00572-x
|View full text |Cite|
|
Sign up to set email alerts
|

Mothers’ knowledge and attitudes about newborn screening in Jordan

Abstract: Newborn screening is an important public health program that helps save the lives of many infants worldwide. The aim of this cross-sectional descriptive study was to examine the knowledge and attitudes of mothers regarding the newborn screening test in Jordan. A convenient sample of 301 mothers of newborns was interviewed to collect data, using structured questionnaires about their knowledge and attitudes regarding the newborn screening. Most mothers exhibited positive attitudes toward the newborn screening. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
(36 reference statements)
2
4
0
Order By: Relevance
“…Procedurally, mothers recalled verbal consent in 69.5% of cases, 12.5% did not recall any consent request, and 18% stated that no consent has been requested. The results on both knowledge and consent practices are similar to somewhat better, compared to other recently reported surveys on this topic [ 11 , 12 , 13 ]. Key HCPs for this knowledge transfer are midwives and nurses, with the leaflet as a supporting resource [ 11 , 14 ].…”
Section: Discussionsupporting
confidence: 86%
“…Procedurally, mothers recalled verbal consent in 69.5% of cases, 12.5% did not recall any consent request, and 18% stated that no consent has been requested. The results on both knowledge and consent practices are similar to somewhat better, compared to other recently reported surveys on this topic [ 11 , 12 , 13 ]. Key HCPs for this knowledge transfer are midwives and nurses, with the leaflet as a supporting resource [ 11 , 14 ].…”
Section: Discussionsupporting
confidence: 86%
“…Only 3 participants felt that eNBS was against their religious beliefs, and eight thought it was not morally acceptable. These findings are on par with Kasem's study in Jordan 13 .…”
Section: Discussionsupporting
confidence: 85%
“…Al-Sulaiman A, et al 12 showed that 91% of women felt NBS was an essential and beneficial public health intervention but only 34% knew that NBS was done to check for a genetic disorder. Furthermore, a study by Kasem A, et al 13 in Jordan in 2020 revealed that most mothers had positive attitudes toward NBS but only moderate knowledge regarding NBS. Paquin RS, et al 14 in 2016 in USA have shown that there is a high parental intention to enrol children into eNBS programmes.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the literature review and the findings of our study, there is strong evidence that NPC educational interventions improve nurses' knowledge and attitudes toward NPC which will benefit the pediatric population in need of NPC facilities by improving their life. The results of this paper concerning the impacts of NPC education intervention provide healthcare professionals with evidence-based data that also indicate their clinical practice as an implementation of skills and reflect on the struggles on those neonates and their parents [25][26][27]. These initiatives can be translated into healthcare and lead to a fundamental change in the standard NPC in Jordan, namely the integration of education into normal treatment [28,29].…”
Section: Discussionmentioning
confidence: 91%